2002
DOI: 10.1152/japplphysiol.01248.2001
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced bronchodilation in natural and induced asthma: effects on ventilatory response and performance

Abstract: We studied whether bronchodilatation occurs with exercise during the late asthmatic reaction (LAR) to allergen (group 1, n = 13) or natural asthma (NA; group 2, n = 8) and whether this is sufficient to preserve maximum ventilation (VE(max)), oxygen consumption (VO(2 max)), and exercise performance (W(max)). In group 1, partial forced expiratory flow at 30% of resting forced vital capacity increased during exercise, both at control and LAR. W(max) was slightly reduced at LAR, whereas VE(max), tidal volume, brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 32 publications
4
43
1
Order By: Relevance
“…In contrast, data in canine isolated airway smooth muscle indicate that it takes almost 8 min for the force to redevelop after an initial stretching (11). In a recent study (6), it was shown that deep breathing on exercise during natural or induced asthma had a bronchodilator effect that was about eight times greater than that of a single deep breath taken at rest. The increase in flow occurred since the first exercise steps and was proportional to the increase in EILV.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, data in canine isolated airway smooth muscle indicate that it takes almost 8 min for the force to redevelop after an initial stretching (11). In a recent study (6), it was shown that deep breathing on exercise during natural or induced asthma had a bronchodilator effect that was about eight times greater than that of a single deep breath taken at rest. The increase in flow occurred since the first exercise steps and was proportional to the increase in EILV.…”
Section: Discussionmentioning
confidence: 96%
“…The observation that some, but not all, asthmatics with normal baseline spirometric results exhibited tidal EFL during exercise is probably related to the fact that some asthmatics exhibit bronchoconstriction during exercise [21][22][23][24][25][26], whereas others do not [26][27][28]. BECK et al [22] had shown that, in asthmatics, there was a reduction in FEV1 during exercise and, subsequently, also demonstrated that, during interval and constant-load exercise, asthmatics exhibit a reduced ventilatory reserve, as well as a higher endexpiratory lung volume (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Epinephrine levels increase during exercise (46) and may influence bronchomotor tone. Crimi et al (47) showed that exercise has a potent bronchodilator effect in subjects with induced or spontaneous asthma. In the healthy athlete, bronchodilation during exercise has been described during studies of exercise performance with and without inhaled b 2 -agonists.…”
Section: Changes In Airway Calibre During Exercisementioning
confidence: 99%